ANALISIS MODEL PREDIKSI KEBANGKRUTAN ALTMAN, ZMIJEWSKI, SPRINGATE DAN GROVER PADA INDUSTRI MANUFAKTUR SUB SEKTOR KIMIA YANG TERDAFTAR DI IDX TAHUN 2013 – 2018 - Sumarna, Enang; Yazid, Helmi; Ichwanudin, Wawan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
In the middle of a fluctuating and competitive economic climate, the industrial sector plays a very important role in supporting the economic life of a country. As an effort to provide initial information on the condition of a company, the bankruptcy prediction model is calculated. This information will be very useful for investors (shareholders) and company management. This study took a sample of the chemical sub-sector manufacturing industry which is highly dependent on fluctuations in the rupiah exchange rate against the US dollar as seen from the origin of imported raw materials and has the aim of implementing the bankruptcy score calculation, testing the consistency of previous research results, conducting different tests from the model and determining the best prediction model. Through the comparative analysis research method using the paired sample t-test, it is concluded that there are significant differences from each of the prediction models used and through two approaches, namely the comparison of calculated scores between the research period before 2019 and in 2019 with an approach based on the auditor's opinion. independent of the financial statements obtained the best model results is the prediction model Zmijewski and Grover. For further research, it can be developed by increasing the number of research samples and a more modern prediction model